Hospital visitors as controls in case-control studies Visitantes hospitalares como controles em estudos caso-controle - Gulnar Azevedo S Mendonça; José Eluf-Neto (Universidade de São Paulo, 2001)
OBJECTIVE: Selecting controls is one of the most difficult tasks in the design of case-control studies. Hospital controls may be inadequate and random controls drawn from the base population may be unavailable. The aim was to assess the use of hospital visitors as controls in a case-control study on the association of organochlorinated compounds and other risk factors for breast cancer conducted in the main hospital of the "Instituto Nacional de Câncer" -- INCA (National Cancer Institute) in Rio de Janeiro (Brazil). METHODS: The study included 177 incident cases and 377 controls recruited among female visitors. Three different models of control group composition were compared: Model 1, with all selected visitors; Model 2, excluding women visiting relatives with breast cancer; and Model 3, excluding all women visiting relatives with any type of cancer. Odds ratios (OR) and 95% confidence intervals were calculated to test the associations. RESULTS: Age-adjusted OR for breast cancer associated with risk factors other than family history of cancer, except smoking and breast size, were similar in the three models. Regarding family history of all cancers, except for breast cancer, there was a decreased risk in Models 1 and 2, while in Model 3 there was an increased risk, but not statistically significant. Family history of breast cancer was a risk factor in Models 2 and 3, but no association was found in Model 1. In multivariate analysis a significant risk of breast cancer was found when there was a family history of breast cancer in Models 2 and 3 but not in Model 1. CONCLUSIONS: These results indicate that while investigating risk factors unrelated to family history of cancer, the use of hospital visitors as controls may be a valid and feasible alternative. OBJETIVO: A seleção de controles é uma das maiores dificuldades nos estudos caso-controle. Controles hospitalares podem ser inadequados, e controles selecionados aleatoriamente na população-base podem ser inacessíveis. Objetivou-se analisar o uso de controles visitantes hospitalares em um estudo caso-controle conduzido no principal hospital do Instituto Nacional de Câncer, no Rio de Janeiro, RJ, que investigou a associação entre compostos organoclorados e outros fatores de risco para câncer de mama feminino. MÉTODOS: O estudo incluiu 177 casos incidentes e 377 controles recrutados entre visitantes mulheres. Três modelos de composição do grupo-controle foram comparados (modelo 1, com todas as visitantes selecionadas; modelo 2, excluindo mulheres que visitavam parentes com câncer de mama; e modelo 3, excluindo todas as mulheres que visitavam parentes com qualquer tipo de câncer). Para testar as associações, foram calculados "odds ratios" e intervalos de confiança de 95%. RESULTADOS: "Odds ratios" de câncer de mama ajustados por idade, associados a fatores de risco que não fossem a história familiar de câncer, com exceção de fumo e tamanho da mama, foram semelhantes nos três modelos. A história familiar de todos os cânceres, exceto mama, mostrou risco diminuído nos modelos 1 e 2, enquanto que no modelo 3, esteve associada ao aumento de risco, porém sem significado estatístico. A história familiar de câncer de mama foi um fator de risco para a doença nos modelos 2 e 3, mas não foi observada associação no modelo 1. Na análise multivariada, risco significante de câncer de mama foi encontrado para história familiar de câncer de mama nos modelos 2 e 3, mas não no modelo 1. CONCLUSÕES: Os resultados indicam que, para investigar os fatores de risco não relacionados à história familiar de câncer, o uso de controles visitantes pode ser uma alternativa válida e viável.